Age-related differences in appetitive trace conditioning and novel object recognition procedures - Marshall, Hayley J.; Pezze, Marie A.; Fone, Kevin C.F.; Cassaday, Helen J. (Neurobiology of learning and memory, 2019)
•Longitudinal study of middle age in the rat with matched younger control cohort.•Appetitive trace conditioning and novel object recognition tests of working memory.•Transient between-groups working memory impairments aged 12 compared with 2 months.•Object exploration reduced with age but working memory recovered.•Object exploration and ITI nosepoking showed some correlation with 5-HIAA/5-HT. Appetitive trace conditioning (TC) was examined over 6 months in younger-adult (2–8 months) and middle-aged (12–18 months) male Wistar RccHan rats, to test for early age-related impairment in working memory. Novel object recognition (NOR) was included as a comparison task, to provide a positive control in the event that the expected impairment in TC was not demonstrated. The results showed that TC improved at both ages at the 2 s but not at the 10 s trace interval. There was, however, evidence for reduced improvement from one day to the next in the middle-aged cohort tested with the 2 s trace conditioned stimulus. Moreover, within the 10 s trace, responding progressively distributed later in the trace interval, in the younger-adult but not the middle-aged cohort. Middle-aged rats showed NOR discriminative impairment at a 24 h but not at a 10 min retention interval. Object exploration was overall reduced in middle-aged rats and further reduced longitudinally. At the end of the study, assessing neurochemistry by HPLC-ED showed reduced 5-HIAA/5-HT in the dorsal striatum of the middle-aged rats and some correlations between striatal 5-HIAA/5-HT and activity parameters. Overall the results suggest that, taken in isolation, age-related impairments may be overcome by experience. This recovery in performance was seen despite the drop in activity levels in older animals, which might be expected to contribute to cognitive decline.